Surface Layer Modification by Cryogenic Burnishing of Al 7050- T7451 Alloy With Near Ultra-Fine Grained Structure - KAYNAK, YUSUF (My University, 2022)
Copyright © 2021 by ASME.Burnishing has been increasingly utilized to improve the surface integrity of manufactured components. The generation of surface and subsurface layers with ultrafine grains, attributed to severe plastic deformation (SPD) and dynamic recrystallization (DRX), leads to improved surface integrity characteristics including surface and subsurface hardness and reduction in surface roughness. Additionally, due to the generation of compressive stresses within the refined layers, increase in fatigue life and improved wear and corrosion resistance can be achieved. In this study, we apply cryogenic burnishing on Al 7050-T7451 discs and compare the surface integrity characteristics with dry conventional burnishing. A special roller burnishing tool with flexible rotating roller head was designed and used to perform the cryogenic burnishing experiments using liquid nitrogen as the coolant. The results show that cryogenic burnishing can increase the surface hardness by an average of 20-30% within a layer depth of 200 μm compared with only 5-10% increase using dry conventional burnishing. Refined layers with nano grain structure were also generated. During cryogenic burnishing, the tangential burnishing forces were higher than those of dry conventional burnishing due to rapid cooling and work hardening of the material.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarım Alet ve Makineleri; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Agricultural Tools and Machines; Engineering and Technology; MÜHENDİSLİK, İMALAT; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); MÜHENDİSLİK, MEKANİK; ENGINEERING, MANUFACTURING; ENGINEERING; Engineering, Computing & Technology (ENG); ENGINEERING, MECHANICAL; Automotive Engineering; Industrial and Manufacturing Engineering; General Engineering; Safety, Risk, Reliability and Quality; Engineering (miscellaneous); Mechanical Engineering; Computational Mechanics; Physical Sciences; cryogenic burnishing; surface integrity; severe plastic deformation; ultrafine microstructure; nontraditional manufacturing processes; process engineering; SEVERE PLASTIC-DEFORMATION; INTEGRITY